Establishment of Standard Reference Environment for Photovoltaic Nominal Operating Cell Temperature Testing with Dedicated Approach for Tropical Region - M.M.M. Hanifah; H. Zainuddin; M.Z. Hussin (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents the establishment of Standard Reference Environment (SRE) for photovoltaic (PV) Nominal Operating Cell Temperature (NOCT) testing in Malaysia representing one of the countries that lies in tropical region. From a field testing conducted, 12-months data of six parameters namely solar irradiance (SI), ambient temperature (AT), relative humidity (RH), wind speed (WS), wind direction (WD), module temperature (MT) and open circuit voltage were analysed to determine the median SI and the median AT.  From the analysis, the median SI and the median AT are 228 W/m2 and 30 °C respectively.  However, these results show that the current approach in determining SRE using median ambient parameters is not suitable for tropical Malaysia based on the percentage error of approximately   30 %. Due to this, the proposed approach applied in this study is determining the corresponding AT of the same SI (800 W/m2) used in present SRE of international standard. Thus, the new proposed SI and AT for SRE in this study are 800W/m2 and 31°C respectively. The SRE found in this study is determined using dedicated approach to suit tropical climate in deriving a more accurate NOCT for tropical region.